A crowdsourcing web system for curating empirical knowledge in Linked Open Data - Yagui, Marcela M. M.; Vivacqua, Adriana S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Traditional and Empirical knowledge databases are becoming essential for the preservation of a region’s culture. Without proper curation this knowledge might be lost over time. The goal of this work is to present a web system to support the co-curation of data derived from empirical knowledge. Our proposal also provides the interconnection between visitors’ contributions with data already available in Linked Open Data repositories. The web system was evaluated by specialists from the Rio de Janeiro Botanical Garden, who verified the impact of the system implantation in cultural environments related to medicinal plants.